Genetic algorithm designed for solving portfolio optimization problems subjected to cardinality constraint - Jalota, Hemant; Thakur, Manoj (International journal of system assurance engineering and management, 2018)
In the present study, a new algorithm named BEXPM-RM is proposed which require no constraint handling techniques to solve portfolio optimization problems subjected to budget, cardinality, and lower/upper bound constraints. The algorithm presented combines the BEX-PM (Thakur et al. in Appl Math Comput 235:292–317, 2014 ) genetic algorithm (GA) together with repair mechanism (RM) proposed by Chang et al. (Comput Oper Res 27(13):1271–1302, 2000 ). BEXPM GA tries to efficiently explore the search space whereas repair method suggested by Chang et al. ( 2000 ) ensures that a solution string is always feasible subject to the budget, cardinality, and lower/upper bound constraints. To analyze the performance of BEXPM-RM, six portfolio optimization problems are considered from the literature (Chang et al. 2000 ; Barak et al. in Eur J Oper Res 228(1):141–147, 2013 ). Among these one problem uses fuzzy set theory and others used probability theory to quantify attributes of a portfolio. In addition to these problems, a new portfolio model is formulated in fuzzy environment to analyze the effect of providing different sets of lower or/and upper bound to an asset.